A preliminary evaluation of naturally occurring radioactivity concentration levels across the State of Kuwait. (March 2016) - Shams, H.; Bajoga, A.D.; Alazemi, N.; Bradley, D.A.; Regan, P.H.
Abstract: An evaluation of naturally occurring radioactive materials has been undertaken as part of a systematic study to provide a surface radiological map of the State of Kuwait. Soil samples were collected from twelve locations across Kuwait and analysed using high-resolution gamma-ray spectrometry. The 226 Ra and 235 U specific activity concentrations have been determined and used to estimate the 235 U/ 238 U isotopic ratios which are found to be comparable to that expected for naturally occurring uranium material. Highlights: Evaluation of NORM from 12 sample locations across the State of Kuwait. Part of a wider, full study to provide a radiological map of Kuwait. Analysis of 226 Ra and 228 Ac decay progeny using HPGe spectrometry. Activity concentrations and isotopic ratios evaluated for 12 locations in Kuwait.